2017
DOI: 10.1182/blood-2016-09-738211
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20-interleukin-21 fusokine targets malignant B cells via direct apoptosis and NK-cell–dependent cytotoxicity

Abstract: Key Points Delivering IL-21 to tumor B cells by fusion with anti-CD20 antibody (αCD20-IL-21 fusokine) is a potent antilymphoma therapeutic strategy. αCD20-IL-21 fusokine demonstrated superior antilymphoma activity compared with its individual components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…We also tested the half-lives of Erb-IL21 and LA22-IL21. Similar to human IgG, the half-lives of both fusion proteins were about 24 hours (Supplemental Figure 2C), while the half-life of native IL-21 was less than half an hour (38). To evaluate whether the antitumor effect of Erb-IL21 is dose dependent, we treated tumor-bearing mice with various doses of Erb-IL21 (25 μg, 75 μg, and 225 μg).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also tested the half-lives of Erb-IL21 and LA22-IL21. Similar to human IgG, the half-lives of both fusion proteins were about 24 hours (Supplemental Figure 2C), while the half-life of native IL-21 was less than half an hour (38). To evaluate whether the antitumor effect of Erb-IL21 is dose dependent, we treated tumor-bearing mice with various doses of Erb-IL21 (25 μg, 75 μg, and 225 μg).…”
Section: Resultsmentioning
confidence: 99%
“…Previous work of ours showed that intratumoral injection of IL-21 could shift tumor macrophages from an M2 to an M1 phenotype and that this resulted in tumor control (37). Unfortunately, the half-life of IL-21 is also very short (37,38), and the intratumoral administration of recombinant IL-21 is rather difficult to administer for most patients.…”
Section: Introductionmentioning
confidence: 92%
“…All procedures performed in studies involving animals were in accordance with the ethical standards of the University of California Los Angeles (UCLA) Animal Research Committee. Murine A20 BALB/c B cell lymphoma line (ATCC) and A20 cells transduced with a lentivirus encoding the human CD20 gene (A20-hCD20, clone R2D2) [34] were cultured in RPMI1640 supplemented with 10% FBS and 50 μmol/L 2-mercaptoethanol (Life Technologies). Human CD20 transgenic mice (hCD20TM), a kind gift from Mark Shlomchik, Yale University, have been described previously [30,34] and were backcrossed onto BALB/c backgrounds and genotypes confirmed by PCR ( Fig.…”
Section: Syngeneic Disseminated B Cell Lymphoma Modelmentioning
confidence: 99%
“…Some strategies have been implemented to sensitize rituximab therapy by combining with other agents to increase the pro-apoptotic effect. These additional agents include macromolecules such as the humanized monoclonal mapatumumab targeting TRAIL-R1 49 , the genetically engineered fusion proteins scFvRit:sFasL 50 , Apo2 ligand (Apo2L)/TRAIL (dulanermin) 51,52 and anti-CD20-interleukin-21 53 , and small molecules, such as the selective NEDD8 activating enzyme inhibitor pevonedistat (MLN4924) 54 , the mTOR (mammalian target of rapamycin) inhibitor temsirolimus 55 , and the proteasome inhibitor bortezomib 56 . However, the efficacy of these agents requires further confirmation or has been suggested to be insufficient based on clinical trials 52 .…”
Section: Discussionmentioning
confidence: 99%